Fostering an Atmosphere of Professionalism in a Residency Program: Learning How to Address the Unprofessional Behavior of Colleagues Through OSCEs - Lita Aeder; Lisa Altshuler; Elizabeth Kachur; Erik Langenau (Association of American Medical Colleges, 2012)
Abstract Introduction Professionalism training and assessment have received much attention. Multiple strategies have been devised to help educational programs deal with unprofessional behavior, which is not always detected by attending staff. Trainees are in a unique position to address unprofessional behavior in their colleagues because of their supervisory role and overlapping working hours. To underline the importance of addressing unprofessional behavior, we created two professionalism objective structured clinical exam (OSCE) stations that focused on confronting a junior level trainee's unprofessional behavior. These two activities are termed the Communications OSCE, for first-year pediatric residents, and the Culture OSCE, for second-year pediatric residents. Methods Prior to the encounter, participants read an instruction sheet and view a short video. In the "Communication with a Colleague" OSCE, participants must confront a junior colleague who treated an ambulance driver disrespectfully. In the "Pediasure Please!" OSCE they have to address a junior colleague who made racist comments about a patient to a medical student. OSCE participants have 10 minutes to complete the task and receive immediate feedback from an observing faculty member and the standardized resident. Post-OSCE group debriefing reinforces the teaching objectives. Following the completion of the OSCE, residents were surveyed anonymously and again 6 to 10 months later to evaluate the effects of the OSCE learning experience. Results The residents were surveyed immediately after the completion of the OSCE. The educational value of the stations was rated moderate to high by 100% and 96% of the first- and second-year students (N = 96), respectively. Six to 10 months after the completion of the exercise, 88% and 76% of the residents still felt that they were to some degree comfortable in dealing with a similar unprofessional encounter as depicted in the OSCE and 88% and 65% in a dissimilar unprofessional encounter. Discussion Our professionalism OSCE station only addresses residents confronting junior residents' unprofessional behaviour. It does not deal with unprofessional behaviour in senior residents, attending staff, or ancillary staff. Our hope is that as the residents graduate to become attending staff, they will take the lessons learned with them and apply them at a higher level of leadership.